Metode Penapisan Kedelai Toleran Salinitas - Pratanti Haksiwi Putri (Puslitbang Tanaman Pangan, 2016)
Soil salinity is due to the dissolved salt in the soil or groundwater. Salinity can be defined as the condition of the soil with EC > 4 dS/m (equivalent to 40 mM NaCl), the osmotic pressure of 0.2 MPa, and the exchangeable sodium percentage (ESP) of <15. Salinity occurs on dry land dry climate and on tidal swamp land near the beach. Saline land area is increasing as a result of land degradation due to various causes. The combination of excessive fertilization, poor irrigation systems and climate change are some of the factors causing salinity. This causes salinity becomes an important issue in the development of agriculture today and in the future. Research on evaluation of soybean resistant to salinity had been done, however, there were some inconsistence results. This paper aimed to review the method of screening for salinity tolerance of soybean, to obtain an appropriate method. Screening for saline-tolerant soybean genotypes need to be done on the entire growth phases of plant, to see the consistency of genotypic resistance to salinity. Things to be considered in screening salinity tolerant in soybean including (1) controlling DHL periodically, (2) the selection of observed variables correlated directly with the saline-tolerant characters, (3) a preliminary test to determine the critical limits of salinity tolerance and (4) to perform molecular screening to reduce the amount of the genotype if the number is too many. The activities should be continued with its physiological screening, to avoid the false result due to the phenotype and genotypes-environment interaction.